Methods of Using Modern Interactive Methods in Teaching a Foreign Language (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the implementation of interactive teaching methods in the instruction of German as a foreign language. Grounded in constructivist and communicative language learning theories, the study highlights the effectiveness of learner-centered, task-based, and technology-integrated strategies in fostering linguistic competence and cultural understanding. Techniques such as gamification, the use of digital platforms, task-based learning, collaborative activities, and multimedia immersion are examined for their pedagogical value in enhancing motivation, engagement, and skill acquisition. Practical examples and classroom applications are provided to demonstrate how interactive methods can simplify complex grammatical structures, such as case systems and verb conjugations, while promoting authentic communication. The article also addresses common challenges in implementing interactive methods and offers practical solutions. Ultimately, the study underscores the transformative potential of interactive strategies in making German language education more effective and accessible.